THE EFFECT OF DIGITAL LEARNING ON SELF-REGULATED LEARNING IN PAI SUBJECTS AT PENGGERAK HIGH SCHOOL - Mubarok, Muhammad Naelul; Harisa, Arizka; Muhit, Abdul; Muqit, Ade Abdul; Rohman, Baeti; Hikmah, Nurul (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The rapid integration of technology in education hastransformed the way student’s access and process learning materials,including in Islamic Religious Education (PAI). Digital learning is expectedto foster greater autonomy, where students are encouraged to take controlof their own learning processes. However, the extent to which digitalplatforms enhance self-regulated learning in PAI subjects still requiresempirical evidence. Purpose: This study aimed to determine the effect ofdigital learning on self-regulated learning in Islamic Religious Education(PAI) subjects for students at Penggerak High School. Method: Theresearchers used quantitative methods. Data were obtained through aseries of observation, documentation, and questionnaire distributionprocesses. Furthermore, the data were processed by conducting statisticaltests through a series of validity, reliability, normality, and simpleregression tests. Result: The results of the study indicate that digitallearning has a significant effect on self-regulated learning. Conclusion:The study concludes that digital learning significantly enhances students’self-regulated learning in PAI subjects. This implies that integrating digitalplatforms can effectively support independent and responsible learningbehavior.